Development of Multimedia Interactive To Improve Early Children's Language Skills - Rulismi, Dwi; Masterjon, Masterjon; Danim, Sudarwan; Kurniah, Nina (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to develop interactive multimedia as teaching materials specifically designed to improve language skills in early childhood. The development method used follows the R&D approach. This study used a sample size divided into two groups. Data was obtained through observation, interviews, and written tests. Data was analyzed using average scores, percentages, and t-tests. where the results of the t-test research that has been carried out are 8.551, then the t-count > t-table value where the t-count is 8.551 from the t-table 2.048. This can be interpreted as significant. The research results show that the interactive multimedia developed is suitable for use in improving language skills in early childhood. This conclusion is based on the results of limited and extensive tests. This development model has proven effective in significantly improving children's language skills. From this research, the researcher concludes that the advantages of developing media in the form of animations, videos, and sound make it more engaging, flexible, and usable online through provided links, and it can also be operated offline using a disk. It also employs attractive cartoon animations that are easy to operate and will be more readily understood by students. Interactive multimedia can capture students' attention and enhance motivation in the teaching and learning process, resulting in improved language skills in learning. This interactive multimedia is equipped with user-operated control tools, allowing users to choose what they desire for the learning process. Additionally, multimedia can also be used to present material using both words and images, where "words" refer to the presentation of the content in a verbal or textual form